2013
DOI: 10.1016/j.jksus.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of single walled carbon nanotubes at subtoxical concentrations on cell adhesion and other cell parameters of human epithelial cells

Abstract: The production of SWCNT has increased tremendously in the last decade, due to high expectations of their benefits. Despite all precautions SWCNT may come into contact with organisms and may be taken up by them. The aim of the present study was to assess and elucidate the effects of SWCNT bundles (purified SWCNT) and SWCNT raw material on the behaviour of human epithelial cells (A549). When cells were exposed to SWCNT (bundles and raw material) cell adhesion was significantly affected. The effects of SWCNT were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…Further, our results confirm previous reports showing that the presence of metal impurities (i.e., Fe) in the nanotube samples resulted in higher cytotoxic and genotoxic effects (Aldieri et al, 2013), production of hydroxyl radicals, loss of intracellular low molecular weight thiols and accumulation of lipid hydroperoxides (Kagan et al, 2006), all by providing quantifiable differential measurements on the cell–cell and cell–substrate interactions without prior cellular manipulation or labeling (Kaiser et al, 2013; Song et al, 2013). …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Further, our results confirm previous reports showing that the presence of metal impurities (i.e., Fe) in the nanotube samples resulted in higher cytotoxic and genotoxic effects (Aldieri et al, 2013), production of hydroxyl radicals, loss of intracellular low molecular weight thiols and accumulation of lipid hydroperoxides (Kagan et al, 2006), all by providing quantifiable differential measurements on the cell–cell and cell–substrate interactions without prior cellular manipulation or labeling (Kaiser et al, 2013; Song et al, 2013). …”
Section: Discussionsupporting
confidence: 89%
“…For instance, analysis showed that internalization of SWCNTs could activate different cellular mechanisms from ROS generation (Aldieri et al, 2013; Jaeger et al, 2012) to inflammation (van Berlo et al, 2014), cell signaling (Ellinger-Ziegelbauer and Pauluhn, 2009), protein expression (Lai et al, 2013), fibrogenesis (Muller et al, 2005; Porter et al, 2010), cellular attachment (Kaiser et al, 2013), viability (Cui et al, 2005) or proliferation (Müller et al, 2011), with such effects being dependent on the length (Manke et al, 2014; Sato et al, 2005), agglomeration (Wick et al, 2007), and surface chemistry (Jiang et al, 2009; Liu et al, 2014) of the nanotubes being tested. However, such methods failed to interpret intermediate exposure time points and mostly defined SWCNT-induced toxicity as invasive cellular changes reflected by cytoskeletal rearrangement (Umemoto et al, 2014), membrane disruption (Chang and Violi, 2006; Umemoto et al, 2014), disruption of the mitotic spindle (Sargent et al, 2012b) and cellular aneuploidy (Sargent et al, 2009; Siegrist et al, 2014), just to name a few.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular uptake, interaction mechanism, and intercellular stability are functions of NP size but still a clear-cut correlation cannot be developed based on available studies. In a summarized way, it can be said that (Helland et al 2008;Mueller and Nowack 2008;Khodakovskaya et al 2009;Fraser et al 2011;Kaiser et al 2012;Han et al 2012;Du et al 2013;Lanone et al 2013;Sarma et al 2014) Amino-polystyrene 20-60 nm (Shiohara et al 2004;Hoshino et al 2004;Yu et al 2006;Hardman 2007;Gagné et al 2008;Valizadeh et al 2012) small size particles are more suspected to cellular internalization and show more toxicity than the larger ones (Hsiao and Huang 2011;Shang et al 2014). …”
Section: Sizementioning
confidence: 99%
“…CNTs have the capacity to adsorb a wide range of proteins, especially those rich in histidine, tryptophan, and phenylalanine [12], and also adhesion proteins from extracellular matrix (fibronectins, collagen) and transmembrane-proteins (integrins) [17]. Since enzymatic cell detachment can produce residual fragments of adhesion proteins, these fragments could interact with CNTs altering the extracellular matrix metabolism which is regulated by a complex mechanism including cell-cell and cell-matrix interactions [13,17].…”
Section: Introductionmentioning
confidence: 99%
“…Since enzymatic cell detachment can produce residual fragments of adhesion proteins, these fragments could interact with CNTs altering the extracellular matrix metabolism which is regulated by a complex mechanism including cell-cell and cell-matrix interactions [13,17]. For this reason, the knowledge of cell-CNTs interactions is essential for cell scaffold development that is used in tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%